Problems of small recreation areas valuation: Forest refugium in the Silesia Park in Chorzów - Damian Panasiuk (Economic and Environmental Studies (E&ES), 2017)
The central part of the Silesia Park in Chorzów was designed as a forest refugium. Now this area of 200 ha is under pressure. Many trees have been cut down for the safety of park visitors. The forest is of significance for people who prefer walking and relaxation far from urban noise and park events. In May 2015, a pilot valuation survey of the forest refugium was conducted using the contingent valuation method (CVM). Respondents were asked if they would be willing to pay a local tax established in consequence of a referendum. Almost half of the respondents did not support implementation of this tax in surrounding towns. The maximum annual tax amount declared by the respondents was 100 PLN, the annual average was 34 PLN and the annual median was 20 PLN. Taking into account the number of residents who totally rejected the tax proposal, the average annual amount was 17 PLN. The forest refugium in the Silesia Park is appreciated by naturalists but is not often visited by the public. This forest area is probably not sufficiently important for the residents to introduce a local tax. The aim of this article is to show restrictions of the use of the CVM method.
Keywords: Q51; Q57; 330; ecosystem valuation; contingent valuation method; the Silesia Park; forest refugium; tree felling